On the modelling aspect of low-velocity impact composite laminates / M.S. Meon...[et al.] - M.S., Meon; N.H., Mohamad Nor; S., Shawal; J.B., Saedon; M.N., Rao; K.-U., Schröder (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Composites suffer a degradation of structural stiffness due to various types of impact loading resulting in damage which is difficult to observe from the surface of the structure. The paper deals with the finite element model (FEM) to study the possible modelling procedures in low-velocity impact (LVI) and failure mechanism of carbon fiber reinforced polymer (CFRP) composite laminate of CCF300/epoxy and its structural responses. In finite element calculation, a proposed three-dimensional progressive damage model is used to determine the intralaminar damage, whereas the cohesive contact formulation is employed to analyse the interlaminar damage. The failure model performances are validated and verified based on different boundary conditions while maintaining the impact energy. Through simulation, the variation in boundary conditions significantly changes the structural responses and energy absorption of the laminates. It is hoped this study will be a great tool in determining the different composite impact scenarios.